PENGELOLAAN UNIVERSAL PRECAUTION DALAM PENCEGAHAN PENYAKIT HIV/AIDS DI RSUD TUGUREJO SEMARANG - Retnaningsih, Dwi (Universitas Muhammadiyah Semarang, 2015)
Forms of Family Support to Mothers With HIV Positive in Compliance With ARV Therapy in The City of Semarang; Health workers have the risk is high enough to be exposed to HIV/AIDS trough splashing of blood or body fluids at a time when the procedure is done at the time of processingor treatment in hospital. In its development of the new policy began called Universal Precaution which aims to prevent transmission between patients and health care personnel either in the hospital or other health services. This study aims to explore the management universal precaution of HIV/AIDS disease prevention in the RSUD Tugurejo Semarang.This research used the qualitative approach with the method of case study research team performed against managers control the prevention of infection in this case team PPI from RSUD Tugurejo Semarang and the officer who runs the execution of the operations. This research showed that Implementation of the universal precaution in RSUD Tugurejo has been since May 2010. From the input factors include human resources, PPI team structure headed by a physician, assisted by 3 people IPCN and IPCLN every office, infrastructure is not yet complete and will be improved completeness, still a global financial organization refers Hospital policies, factors of process that includes planning work program refers to the guide books, organizing, and controlling; factor output is seen from a number of health care personnel who apply universal precaution; and the feedback factor include surveillans and evaluation in the implementation on the ground is still based on the PPI manual and have not adapted to the conditions in the RSUD Tugurejo that are still in the process of adaptation, development and repair. Human resources have enough like standard. Financial programme haven’t made specific yet. The completeness of tools have been improved day by day. A little of policy still uses manual from central.Planning, organizing and controlling grounded on manual and be appropriated with field condition. According IPCN data, all of health worker obedient in to universal precaution implementation. Surveillans and evaluation did each month with continued data invention socialiszation.Keywords : Universal Precaution, HIV/AIDS, RSUD Tugurejo